Strategy and Tactics of World Communism.: hearings before the United States Senate Committee on the Judiciary, Subcommittee To Investigate the Administration of the Internal Security Act and Other Internal Security Laws, Eighty-Fourth Congress, first session, Eighty-Fourth Congress, second session. - United States. (U.S. G.P.O., 1955)
Investigates statements in Harvey M. Matusow's book "False Witness" that he repeatedly gave false information while acting as an informant for congressional committees investigating communist activities.
Record is based on bibliographic data in CIS US Congressional Committee Hearings Index. Reuse except for individual research requires license from Congressional Information Service, Inc.
Indexed in CIS US Congressional Committee Hearings Index Part VI
Investigates statements in Harvey M. Matusow's book "False Witness" that he repeatedly gave false information while acting as an informant for congressional committees investigating communist activities.
Keywords: Governmental investigations / United States.; False testimony / United States.; Communist strategy.